Estimation of Crop Water Requirement and Crop Planning for Vi gin Arid Lands under Canal Command - Joshi, N L; Singh, Y V (Annals of Arid Zone, 2016)
Irrigation planners need information on crop water requirement for project planning in command area. Under Indira Gandhi NaharÂ· Project stage-II about 1.012 M ha area would come under irrigation. The estimated annual evapotranspiration (ET) demand in Indira Gandhi Nahar Project stage-II area ranged between 1833 mm and 2897 mm. The maximum reference ET of 2897 mm in laisalmer district was due to the harsh climatic conditions of the region, while the minimum annual ET of 1833 mm for Ganganagar district was due to the boundary effects of developed irrigated agriculture. Variations in the water requirement of various crops in different districts was estimated. In the absence of detailed field experimentation, modified Penman method was found appropriate for estimation of water requirement of crops in the command area. With an overall irrigation intensity of 87 per cent, 354200 ha under kharif, 474140 ha under rabi and 50600 ha under perennial cropping was found appropriate, based on water availability constraint factors.